Characterization of the complete mitochondrial genome sequence of Homatula potanini (Cypriniformes, Nemacheilidae, Nemachilinae). (3rd March 2016) - Que, Yan-Fu; Tang, Hui-Yuan; Xu, Nian; Xu, Dong-Mei; Shi, Fang; Yang, Zhi; Li, Wei-Tao
Abstract: Homatula potanini is an endemic and one of ornamental fishes in the upper stream of the Yangtze River and its tributaries. However, wild populations of H. potanini declined sharply due to anthropological activity in the Jinsha River during the past decades. In present study, the complete mitochondrial DNA genome sequence of H. potanini was first determined by DNA sequencing based on the PCR fragments. The complete mitochondrial genome sequence is a circular molecule of 16, 569 bp in size. It consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region (D-loop). The gene nucleotide composition of H. potanini is 30.1% A, 26.9% C, 16.7% G, and 26.3% T, with a relatively high A + T content (56.4%). The results could provide useful data for studies on genetic structure and rational resource conservation in H. potanini .